Whaling in the Antarctic. (2018) - Unknown
Abstract : Environment — Marine environment — Whaling — International Convention for the Regulation of Whaling, 1946 — International Whaling Commission — Schedule to the Convention — Moratorium on commercial whaling — Article VIII of the Convention — Exemption for whaling carried out for purposes of scientific research — Dispute between Australia and Japan concerning Japan's continued pursuit of large-scale whaling programme — Japanese Whale Research Program under Special Permit in the Antarctic ("JARPA II") — Effect on whale stocks — Whether Japan breaching its obligations under the Convention — Whether Japan breaching its other international obligations for preservation of marine mammals and marine environment Treaties — Interpretation — International Convention for the Regulation of Whaling, 1946, Article VIII(1) — Scope of Article VIII(1) — Whether special permits granted by Japan in connection with Japanese Whale Research Program under Special Permit in the Antarctic ("JARPA II") "for purposes of scientific research" — Object and purpose — Whether restrictive or expansive interpretation justified — Discretion of State Party — Standard of review — Whether, in using lethal methods, programme's design and implementation reasonable to achieve stated objectives — Task of Court — Meaning of phrase "for purposes of scientific research" — Schedule to Convention — Duty of cooperation with International Whaling Commission and Scientific Committee — Whether Japan breaching its obligations under International Convention for the Regulation of Whaling, 1946 — Whether Japan breaching its other international obligations for preservation of marine mammals and marine environment — Remedies International Court of Justice — Intervention — Article 63(2) of Statute conferring right to intervene as a non-party in proceedings — Declaration of Intervention filed by New Zealand in case between Australia and Japan regarding whaling — Whether Declaration fulfilling requirements of Article 63 of Statute and Article 82 of Rules — Whether Declaration admissible International Court of Justice — Jurisdiction — Optional clause — Reservations — Reciprocity — Whaling dispute between Australia and Japan — Whether falling within Australia's reservation